THE INFLUENCE OF SUSTAINABLE PRACTICES IN THE HOSPITALITY INDUSTRY ON CONSUMER DECISION-MAKING - Julija Mironova; Inguna Zusevica; Zaiga Oborenko (Baltic Journal of Economic Studies)
Sustainability has become an integral part of business strategies, influencing both operational decisions and customer choices. As people become more aware of environmental and social issues, many are looking for hospitality services that align with their values. But how much do sustainability efforts actually influence customers' choices of where to stay? This study explores this question by analysing whether sustainable practices in the hospitality industry influence consumer preferences. In order to comprehend the aforementioned correlation, the authors of this study conducted a survey with the objective of acquiring insights into customer attitudes towards sustainability in the hospitality industry. The survey encompassed pivotal domains such as eco-friendly initiatives, energy efficiency, waste reduction, ethical sourcing, and corporate social responsibility (CSR). Utilising the statistical software SPSS, the authors employed descriptive statistics and Kruskal-Wallis non-parametric tests to examine whether hotel sustainability practices have a greater impact on the decision-making process of customers with higher education compared to those with lower education levels. The findings of the study demonstrate that sustainability is a significant consideration for customers. Individuals are more inclined to select hotels that demonstrate a commitment to meaningful sustainability initiatives. Moreover, the data indicates that consumers with a higher educational background place a greater value on sustainability when making their decisions. This research underscores the mounting significance of sustainability as a competitive advantage in the hospitality sector. Companies that integrate strong and transparent sustainability practices not only help the planet, but also attract a more loyal and conscious customer base. These findings provide valuable guidance for hospitality managers and policymakers, emphasising the need for sustainability initiatives that are both impactful and well communicated.